2023
DOI: 10.33503/ebio.v8i02.2785
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the correlation between critical thinking and metacognitive skills of senior high school students in biology Jeneponto Regency, South Sulawesi, Indonesia

Rahmat Saleh,
Filawati Filawati,
Adriani Adriani
et al.

Abstract: There is a need to map the connection between critical thinking and metacognitive skills of high school students so that educators can determine learning steps to help students obtain optimal learning outcomes and 21st-century skills. The research objective is to Examine the relationship between high school biology students' metacognitive abilities and critical thinking education. It is a quantitative-correlational study. The research sample was 230 grade XI students pursuing science specialization obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Research has demonstrated the positive impacts of learning motivation on critical thinking skills [105][106][107], and highlighted the importance of motivation in cultivating critical thinking dispositions oriented towards learning [108]. For instance, studies have found that students with high academic motivation are interested in problem-solving and critical thinking, leading to greater perfectionism and positive effects on their cognitive abilities and academic performance [109].…”
Section: H5: General Self-efficacy Has a Positive Impact On Learning ...mentioning
confidence: 99%
“…Research has demonstrated the positive impacts of learning motivation on critical thinking skills [105][106][107], and highlighted the importance of motivation in cultivating critical thinking dispositions oriented towards learning [108]. For instance, studies have found that students with high academic motivation are interested in problem-solving and critical thinking, leading to greater perfectionism and positive effects on their cognitive abilities and academic performance [109].…”
Section: H5: General Self-efficacy Has a Positive Impact On Learning ...mentioning
confidence: 99%